Factors associated with farmers’ adoption of standardized planting methods: evidence from China - Hu, Chenxia; Li, Lingyu; Wright, Alan L.; Zheng, Qiaoqiao; Li, Nanyang; He, Shan (Frontiers in Sustainable Food Systems, 2024)
The standardization of planting techniques has substantially enhanced production efficiency and agricultural output. Understanding farmers’ perceptions and adoption of standardized planting practices is essential. In this study, the questionnaire responses of 244 farmers from Zhejiang Province, China, revealed their predominantly positive perceptions of standardized planting methods. More than half of the respondents were engaged in standardized planting at the time of the survey. Farmers’ planting experience and participation in cooperatives significantly affected their perceptions. The binary logistic model was implemented to explore the factors influencing farmers’ adoption of standardized planting methods. The results of the regression analysis revealed that significant influencing factors included farmers’ education level, planting experience, participation in cooperatives, awareness of standardized planting methods, the perceived effects of standardized planting methods on household income and on village ecological environment. The interpretive structural model was furtherly employed to analyze the hierarchical structure and internal mechanisms of the influential factors. The results revealed that the surface level factors influencing farmers' adoption of standardized planting methods were farmers’ village cadre status, participation in cooperatives, and awareness of standardized planting methods. Farmers’ education level and planting experience were the fundamental factors. This study promotes the adoption of standardized planting methods and their enhanced implementation.